Analisis Strategi Pemasaran pada PT Astra Internasional Tbk - Shintami Oktavia; Hasiandra Simanjuntak; Putri Sandrina Sitompul; Radhika Narwastu; Maya Martiza Sari; Cecilia Miranda Lumbangaol; Dicky M.C Sinulingga (Departement of Mathematics Education, 2024)
Information within a company is very important to support sustainability development, so there is a reason that information is really needed for a company company. One company that uses an integrated information system network to make business easier the company is PT. Telkom . Telkom demands to be even better improve the quality and quantity of its services in order to become a company the best telecommunications in Indonesia and even the world, not only that, PT Telkom too Realizing that there is the importance of human resources (HR) in helping company to achieve its main targets, and in helping the company to achieve main target, and in its implementation must take into account social interests, functional and employee.